Importance of Lipopolysaccharide and Cyclic β-1,2-Glucans in Brucella-Mammalian Infections - Andreas F. Haag; Kamila K. Myka; Markus F. F. Arnold; Paola Caro-Hernández; Gail P. Ferguson (International Journal of Microbiology)
Brucella species are the causative agents of one of the most prevalent zoonotic diseases: brucellosis. Infections by Brucella species cause major economic losses in agriculture, leading to abortions in infected animals and resulting in a severe, although rarely lethal, debilitating disease in humans. Brucella species persist as intracellular pathogens that manage to effectively evade recognition by the host's immune system. Sugar-modified components in the Brucella cell envelope play an important role in their host interaction. Brucella lipopolysaccharide (LPS), unlike Escherichia coli LPS, does not trigger the host's innate immune system. Brucella produces cyclic β-1,2-glucans, which are important for targeting them to their replicative niche in the endoplasmic reticulum within the host cell. This paper will focus on the role of LPS and cyclic β-1,2-glucans in Brucella-mammalian infections and discuss the use of mutants, within the biosynthesis pathway of these cell envelope structures, in vaccine development.